Avaliação dos mecanismos envolvidos na ação antinociceptiva causada pelo seleneto vinílico bis substituído (SVBS) em camundongos - Jesse, Cristiano Ricardo (2009)
The interest in organoselenium biochemistry and pharmacology has increased in the last two decades due to a variety of organoselenium compounds that possess biological activity. Accordingly, bis selenide is known as a safe drug when administered acutely to mice at doses that have antiinflammatory and antinociceptive activities. Therefore, the search for the mechanisms by which this compound exerts its effects is extremely important for the therapeutic application. Based on the considerations above, the aims of the present study were to evaluate the antinociceptive properties, as well as the possible mechanisms involved in this process. The oral administration of bis selenide caused significant inhibition of the biting behavior induced by intrathecal (i.t.) injection of glutamate, kainate, (±)-1-aminocyclopentane-trans-1,3-dicarboxylic acid (trans-ACPD), capsaicin, substance P (SP), interleukin 1β (IL-1β) and tumor necrosis factor-α (TNF-α) but completely failed to affect the nociception induced by α-amino-3-hydroxy-5-mehtyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA). In addition, the oral administration (p.o.) of bis selenide caused a significant increase in hot plate (55 °C) response latency. The antinociceptive effect caused by bis selenide in the hot plate test was reversed by i.t. injection of several K+ channel blockers tetraethylammonium (TEA, non-selective voltage-dependent K+ channel inhibitor) and glibenclamide (ATP-sensitive K+ channel inhibitor) but was not significantly reversed by pretreatment of animals with apamin and charybdotoxin (large- and smallconductance Ca2+- activated K+ channel inhibitors, respectively). These results suggest the participation of glutamatergic, peptidergic and vanilloid systems and potassium channel in the antinociceptive action caused by bis selenide in mice.